EFEKTIVITAS PROMOSI MUSEUM BENTENG VREDEBURG MELALUI MEDIA SOSIAL INSTAGRAM @MUSEUM.BENTENG.VREDEBURG DENGAN ANALISIS MODEL ATR - Putri Meliana Ariyani (Jurnal Pariwisata Indonesia, 2023)
The effectiveness of promotion through Instagram Social Media is related to how to design messages in marketing communications and how followers respond and act on messages that are made. The response given by followers is related to the decision to use the supported product. So that the effectiveness of promotion is determined by the objectives of marketing communications and the response of the followers. This study aims to determine the effectiveness of the promotion of the Fort Vredeburg Museum through the social media Instagram @museum.benteng.vredeburg based on the ATR Model. The approach used in this research is descriptive quantitative with a questionnaire method that includes indicators of awareness, trial and reinforcement. The results of this study indicate that the promotion effectiveness of the Fort Vredeburg Museum through Instagram Social Media @musem.benteng.vredeburg according to awareness is 77.23%; trial 73.24%; and strengthening 69.98%. Social media Instagram @museum.benteng.vredeburg as a quite effective ATR Model-based product promotion media. with a result of 72.7% of the average count of all levels.